Comparative genomic analysis of crustacean hyperglycemic hormone (CHH) neuropeptide genes across diverse crustacean species - Chang, W; Lai, A (F1000, 2018)
Background Recent studies on bioactive peptides have shed light on the importance of these compounds in regulating a multitude of physiological, behavioral and biological processes in animals. Specifically, the neuropeptides of the crustacean hyperglycemic hormone (CHH) superfamily is known to control a number of important functions ranging from energy metabolism, molting, osmoregulation to reproduction. Methods Given the importance of this peptide family, we employed a conservative approach utilizing extant transcriptome datasets from 112 crustacean species, which not only include important food crop species from the order Decapoda, but also from other lower order crustaceans (Branchiopoda and Copepoda), to identify putative CHH-like sequences. Results and conclusions Here we describe 413 genes that represent a collection of CHH-like peptides in Crustacea, providing an important staging point that will now facilitate the next stages of neuroendocrine research across the wider community.